Issues of Improving the Provisions of the Current Law of Ukraine Regarding the Prevention of the Origin and Spread of COVID-19 Coronavirus Disease - K. L. Buhaichuk (Law and Safety)
The author has studied the current state of the regulatory base on the prevention of the occurrence and spread of the COVID-19coronavirus disease in Ukraine and the practice of its application by authorized entities for the implementation of state policy in the field of health care and the protection of the rights and freedoms of citizens.